If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 36 = 4x + -50 Reorder the terms: 36 + 3x = 4x + -50 Reorder the terms: 36 + 3x = -50 + 4x Solving 36 + 3x = -50 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 36 + 3x + -4x = -50 + 4x + -4x Combine like terms: 3x + -4x = -1x 36 + -1x = -50 + 4x + -4x Combine like terms: 4x + -4x = 0 36 + -1x = -50 + 0 36 + -1x = -50 Add '-36' to each side of the equation. 36 + -36 + -1x = -50 + -36 Combine like terms: 36 + -36 = 0 0 + -1x = -50 + -36 -1x = -50 + -36 Combine like terms: -50 + -36 = -86 -1x = -86 Divide each side by '-1'. x = 86 Simplifying x = 86
| 9(4b-4)=2(9b+3) | | 2.5+15+0.5(x-4)=1.2x+2(0.9x-6) | | 5y=7y-2 | | 5-3.45= | | .5y=1.4 | | y=-2.5x-5 | | 20x-3=36x+1 | | 2x+25=34 | | 6+9.33= | | 2(5x+9)=-30+8 | | 2x(5x+9)=-30+8 | | -7x-12(x*9)=-2(9x+7) | | .2x+8=-.6666667x-2 | | 8a+a-7-15a= | | 3x+2(x-1)=9x+4 | | y=-2.1x-5 | | .333x+(x-10)+(x-20)+40=30 | | 0.20x+0.50(120)=0.40(x+120) | | 63+3x=-4x | | 4x^2+28x-12=0 | | 2(4x+6)=-41+29 | | 0.40(80)+0.10x=0.30(x+80) | | 9(x+3)=9 | | 2p^2-12p-14=0 | | 8st-28t-10s-35=0 | | -48=5v+4 | | 3(x-4)=3x-2 | | -63=9s | | K-32+(-16)=-9 | | 8=5p+13 | | 15=2x-7 | | m(1.50)+5=15.50 |